Предмет: Математика,
автор: fest1997
lg(3x^2+28)-lg(3x-2)=1
Ответы
Автор ответа:
0
lg(3x^2+28)-lg(3x-2)=lg10
lg(3x^2+28)/(3x-2)=lg10
(3x^2+28)/(3x-2)=lg10
30х-20=3x^2+28
3x^2-30х+48=0
x^2-10х+16=0
D=100-64=36
х1=2 х2=8
lg(3x^2+28)/(3x-2)=lg10
(3x^2+28)/(3x-2)=lg10
30х-20=3x^2+28
3x^2-30х+48=0
x^2-10х+16=0
D=100-64=36
х1=2 х2=8
Похожие вопросы
Предмет: История,
автор: lolita567123
Предмет: География,
автор: kabaN04
Предмет: Английский язык,
автор: Maxim33333
Предмет: Математика,
автор: marinka200211